Activities of Asri Kadin Cemiyeti During the Armistice Period (1918–1923) - Nuray Özdemir (Yakın Dönem Türkiye Araştırmaları)
Asri Kadın Cemiyeti (Association of Modern Women) was one of the most effective women’s associations during the National Struggle period. Founded in Istanbul at the end of 1918 by graduates and students of İnas Darülfünunu (Women’s University), its aims were to educate women physically and mentally and to raise their social status. Naciye Faham, Şukufe Nihal, Aliye Esad, Sabahat, and Saime Hanım were outstanding figures in the Association. The first meeting to protest the occupations was organized immediately after the Armistice of Mudros and was held in Fatih Tomb on March 19, 1919 under the leadership of Asri Kadın Cemiyeti. The Association also supported protests held in Üsküdar,Kadıköy, and Sultanahmet against the occupation of İzmir. During these protests, members of the Association delivered impressive speeches. The Association could take little action after the official occupation of Istanbul. This study engages in research into the activities of Asri Kadın Cemiyeti during the armistice period. Its objective is to evaluate the role of women, organized through associations in the face of occupation, in winning the National Struggle.